INTERNAL CONTROL SYSTEM IN THE ORGANIZATION: NATIONAL AND INTERNATIONAL EXPERIENCE - Dyshlovoy, Igor; Shevchuk, Andrey; Nekhaychuk, Dmitry; Kotelevskaya, Yulia; Fomina, Elena (Revista Inclusiones, 2020)
This study is dedicated to arranging the internal control system in the organization. The authors have generalized approaches to the scientific interpretation of the internal control concept. The main international documents for internal control have been systematized. Comparative escriptions of internal audit, internal control, and supervision and auditing services have been analyzed. It has been shown that any management function is consolidated with the control function and control itself is closely combined with other elements of management in practice. The implementation of daily control involves reporting, accounting, monitoring, access rights to assets, and separation of powers. The main elements of the internal control concept, basic principles and approaches to building an internal control system have been identified in the course of this study. The main advantages and disadvantages of internal control building systems have been revealed.